2021
DOI: 10.3390/diagnostics11081397
|View full text |Cite
|
Sign up to set email alerts
|

The Associations of Periodontopathic Bacteria and Oral Candida with Periodontal Inflamed Surface Area in Older Adults Receiving Supportive Periodontal Therapy

Abstract: The periodontal inflamed surface area (PISA) has been proposed for assessment of the total periodontal inflammatory status in people with periodontitis. This study was performed to investigate the associations of periodontopathic bacteria and candida with PISA in older people. We enrolled 100 patients aged ≥ 60 years who visited Hiroshima University Hospital. PISA and periodontal epithelial surface area (PESA) were calculated in each patient. Oral rinse samples were collected for DNA extraction. Periodontopath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…The results highlight the importance of co-infection with red complex bacteria in periodontal inflammation severity. In contrast, no significant association was found between P. gingivalis and PISA values in participants after adjustment for their potential confounding factors [25]. Thus, P. gingivalis may determine the severity of periodontitis in cooperation with other periodontopathic pathogens such as C. albicans.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…The results highlight the importance of co-infection with red complex bacteria in periodontal inflammation severity. In contrast, no significant association was found between P. gingivalis and PISA values in participants after adjustment for their potential confounding factors [25]. Thus, P. gingivalis may determine the severity of periodontitis in cooperation with other periodontopathic pathogens such as C. albicans.…”
Section: Discussionmentioning
confidence: 81%
“…The relationship between periodontopathic bacteria and PISA values was previously investigated in participants after adjustment for their potential confounding factors using propensity scores [25]. Participants with co-infection of Tannerella forsythia and Treponema denticola exhibited significantly higher PISA values than those without such co-infection [25].…”
Section: Discussionmentioning
confidence: 99%
“…albicans has been co-located with periodontopathogens such as Porphyromonas gingivalis, Tannerella forsythia and Treponema denticola in sites of periodontitis. Importantly, periodontal sites from which the fungus was co-isolated with either T. forsythia or T. denticola appeared to display a greater surface area of inflammation, suggesting a synergism between the bacteria and fungus triggering periodontal tissue damage [13]. Of all the periodontal bacterial pathogens, the interactions between P. gingivalis and C. albicans have been explored in most depth.…”
Section: Periodontal Diseasementioning
confidence: 99%
“…Lately, the role of yeast and its crosskingdom interaction with various bacteria in periodontitis pathogenesis were discussed. Investigation of the associations of Candida and periodontopathic bacteria from seniors (≥60 years old) demonstrated that the surface area of inflamed periodontal tissue was significantly greater when T. forsythia and T. denticola were detected together with C. albicans from patients (Shigeishi et al, 2021). Also, several studies revealed various interaction mechanisms between C. albicans and P. gingivalis.…”
Section: Periodontitismentioning
confidence: 99%